Biomarkers of intestinal epithelial damage in children with food allergies - Rycyk, Artur; Lebensztejn, Dariusz; Cudowska, Beata (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Food allergy has a significant negative impact on patients and their families, and it has become an important public health problem. Currently used diagnostic methods, such as skin prick tests (SPT) and determination of specific immunoglobulins E (sIgE), present limited sensitivity and specificity. Therefore, new tools are expected to improve the accuracy of the diagnostic work-up. A recent hypothesis of allergic reactions indicates a primary role of dysregulation of the epithelial barrier, which pioneers the role of biomarkers of intestinal damage in food allergy. The objective of this paper is to present the currently most promising biomarkers for the diagnosis, prognosis, and management of food allergy in children.